2017
DOI: 10.1002/bsl.2273
|View full text |Cite
|
Sign up to set email alerts
|

Memory Errors in Alibi Generation: How an Alibi Can Turn Against Us

Abstract: Alibis play a critical role in the criminal justice system. Yet research on the process of alibi generation and evaluation is still nascent. Indeed, similar to other widely investigated psychological phenomena in the legal system - such as false confessions, historical claims of abuse, and eyewitness memory - the basic assumptions underlying alibi generation and evaluation require closer empirical scrutiny. To date, the majority of alibi research investigates the social psychological aspects of the process. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 64 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…Experiment 2: Alibi discrimination and evaluation The proposition that innocent people can generate accurate alibis supported with strong evidence (Olson & Charman, 2012) raises the possibility that those who are not innocent cannot generate accurate alibis with strong supportive evidence. However, as described above, there are various reasons why nonoffenders would not report an accurate alibi (Crozier et al, 2017). In addition, alibi generation research shows that the strength of the supportive evidence cannot be used on its own to determine the believability of an alibi because most non-offenders do not have such strong evidence although they are innocent (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiment 2: Alibi discrimination and evaluation The proposition that innocent people can generate accurate alibis supported with strong evidence (Olson & Charman, 2012) raises the possibility that those who are not innocent cannot generate accurate alibis with strong supportive evidence. However, as described above, there are various reasons why nonoffenders would not report an accurate alibi (Crozier et al, 2017). In addition, alibi generation research shows that the strength of the supportive evidence cannot be used on its own to determine the believability of an alibi because most non-offenders do not have such strong evidence although they are innocent (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the alibi should be correct and supported by strong evidence. True alibis can, however, also be inaccurate because of various reasons (Crozier et al, 2017). It has been demonstrated that the larger the time gap between the alleged crime and the moment of interviewing, the more errors occur in the alibi statement of non-offenders (e.g.…”
Section: Alibi Researchmentioning
confidence: 99%
“…Regardless of the guilt/innocence presumption with which interviewers approach suspect interviews, innocent suspects sometimes fail to provide convincing alibis due to the reporting of incomplete and/or inaccurate details (Olson & Charman, ; Olson & Wells, , ). During a crime investigation, innocent suspects whose alibi turns out to be erroneous or incomplete may be perceived as liars (Burke, Turtle, & Olson, ; Dysart & Strange, ; Olson & Charman, ), and, ultimately, are at increased risk of being falsely convicted (Crozier, Strange, & Loftus, ; Wells et al, ). Thus, unintentionally providing inaccurate alibis can be very risky for innocent suspects.…”
Section: Introductionmentioning
confidence: 99%
“…Another context in which people are asked to list places visited and people encountered is generating true alibi statements to a crime (e.g., Allison, Michael, Mathews, & Overman, 2011;Crozier, Strange, & Loftus, 2017;Culhane, Hosch, & Kehn, 2008;Culhane et al, 2013;Olson & Charman, 2012). In fact, there are many different facets of providing an alibi that are similar to reporting during contact tracing.…”
Section: Application To Alibi Statementsmentioning
confidence: 99%
“…In eyewitness memory research the participant is often aware that the information presented is likely to be requested later. However, in generating an alibi, the individual is typically recalling everyday events for which he or she did not pay attention and therefore has difficulty remembering later (Crozier, Strange, & Loftus, 2017). Reporting an alibi is also unique to other types of reporting because it asks individuals to remember autobiographical events, which often occur repeatedly (i.e., a person trying to remember details about one specific instance (e.g., driving to school last Tuesday) amongst all other instances (e.g., driving to school on Thursday, or on the Tuesday before)).…”
Section: Application To Alibi Statementsmentioning
confidence: 99%